Ambulation status at an acute care hospital predicts pneumonia and mortality in stroke patients: A retrospective cohort study. Issue 8 (15th June 2022) - Yamauchi, Kota; Kumagae, Kenichi; Goto, Kei; Harayama, Eisei; Tanaka, Shota; Hagiwara, Risa; Uchida, Yoshiko; Kuroyama, Sota; Koyanagi, Yasuhiro; Arakawa, Shuji
Abstract : Aim: Higher post‐stroke functional performance is associated with lower mortality in patients with stroke. This study aimed to investigate the relationship between ambulation ability in the acute phase of stroke, and pneumonia and mortality 1 year after stroke onset. Methods: This retrospective cohort study included consecutive stroke patients between April 2008 and December 2018. Patients were divided into six groups according to their Functional Ambulation Category score at discharge (0 [unable to walk] to 5 [able to walk independently]). We observed pneumonia cases and all‐cause mortality over 1 year, and investigated the association between Functional Ambulation Category score and pneumonia or mortality. Survival analysis was carried out using Kaplan–Meier curves, log‐rank tests and Cox regression models. Results: We analyzed 1727 consecutive patients (median age 77 years; 54% men). During the observation period, 144 patients (8.3%) experienced pneumonia and 157 (9.1%) died. Increasing ambulatory impairment showed stepwise relationships with the risk of pneumonia and mortality. Compared with patients with a Functional Ambulation Category score of 5, those with scores of 4 and 3 showed no significant association with pneumonia risk; a score ≤2 was significantly different. There was a stepwise relationship between increased gait disturbance and risk of death compared with the Functional Ambulation Category 5 group. Conclusions: Ambulation ability at discharge from an acute hospital is an important predictor of pneumonia incidence and survival in stroke patients at 1 year; these associations were observed even after controlling for clinical parameters, such as stroke severity and comorbidity. Geriatr Gerontol Int 2022; 22: 554–559 . Abstract : Ambulation ability at discharge from an acute hospital is an important predictor of pneumonia incidence and survival in stroke patients at 1 year.